THE USE OF MIX AND MATCH GAME TO TEACH READING NARRATIVE TEXT TO THE EIGHTH GRADERS OF SMP NEGERI 1 TANGGULANGIN (RETAIN, 2013)
Reading is receptive skill that has to be mastered by students. It is one of the important subjects that will be tested in national exam. Therefore, teachers introduce many media to help the students easily understand in reading text. One of interesting media to teach reading narrative text is mix and match game. In this case, the Thus, this paper will describe the use of mix and match game in teaching reading narrative text to eighth graders of SMP Negeri 1 Tanggulangin. This media is a game that conducted in a group. There are some question and answer cards which are written in different cards. This game needs some cards which are divided into some categories. There are a set of word cards with meaning cards and a set of question cards and answer cards. This study is expected to make the teachers able to apply the media in this study when teaching reading narrative text in the class. A descriptive qualitative research was used to conduct this study and the observation checklist, field note, questionnaire and students’ worksheet were the instruments to collect the data. The result showed the media used by the teacher to teach reading narrative was interesting media which can build enjoyable environment. This media can be implemented as a media to teach reading narrative text to the eighth graders of SMP Negeri 1 Tanggulangin. This media makes students’ reading comprehension become better. Keywords: media, teaching reading, mix and match game